2011
DOI: 10.1590/s0100-204x2011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de frangos de corte e digestibilidade de rações com sorgo ou milheto e complexo enzimático

Abstract: Resumo -O objetivo deste trabalho foi avaliar a digestibilidade de rações formuladas com sorgo (Sorghum bicolor), ou milheto (Pennisetum glaucum) e adição de um complexo enzimático comercial composto de amilase, carboidrases, proteases e fitase, e o desempenho de frangos de corte. Para avaliação de desempenho, foram alojados 1.800 pintos de corte machos em delineamento em blocos ao acaso, em arranjo fatorial 2x2, com quatro tratamentos (rações com sorgo ou milheto com ou sem adição de complexo enzimático) e ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
4
10
0
6
Order By: Relevance
“…These results also confirm that the use of enzymes in corn-and soybean meal-based broiler diets promote better performance (p<0.01) by breaking down the antinutritional factors present in the cell wall of plants (Graham et al, 2002), and hence, better nutrient absorption and animal performance (Costa Leite et al, 2011;Powell et al, 2011;Walk et al, 2012).…”
Section: Discussionsupporting
confidence: 72%
“…These results also confirm that the use of enzymes in corn-and soybean meal-based broiler diets promote better performance (p<0.01) by breaking down the antinutritional factors present in the cell wall of plants (Graham et al, 2002), and hence, better nutrient absorption and animal performance (Costa Leite et al, 2011;Powell et al, 2011;Walk et al, 2012).…”
Section: Discussionsupporting
confidence: 72%
“…Brito et al (2006), using an enzyme complex containing amylase, protease, and xylanase, observed increased weight gain and improved feed conversion ratio in broilers between 1 to 21 days of age, as opposed to the findings of the present experiment. In addition, Leite et al (2011), who evaluated the same enzyme complex as the current study, found better feed conversion ratio 21-d-old broilers.…”
Section: Enzyme Supplementation Of Broiler Feeds With Reduced Mineralsupporting
confidence: 58%
“…The positive response achieved by phytase, protease and xylanase supplementation during starting phase are agreement with Brito et al, (2006) and Leite et al, (2011) who noted that, adding enzyme complex containing protease, and xylanase increased weight gain and improved FCR in broilers between 1 to 21 days of age. Also, Olukosi et al, (2007) found increase in weight gain, of broiler (1-21 d) fed corn-soybean diet low in energy (-115 kcal),Ca (-0.11%) and available P (-0.10 %) when added mixed enzymes (xylanase, amylase and protease) or phytase enzyme individually or in combination.…”
Section: Resultssupporting
confidence: 86%